1978
DOI: 10.1111/j.1365-2125.1978.tb01608.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of atenolol and oxprenolol in patients with angina or hypertension and co‐existent chronic airways obstruction.

Abstract: 1 The effects of atenolol (50 mg and 100 mg) and oxprenolol (80 mg) on respiratory function were studied in ten patients with angina pectoris or hypertension complicated by chronic airways obstruction. 2 In patients with “fixed” airways obstruction, neither atenolol nor exprenolol significantly affected airways resistance. 3 In patients with “labile” airways obstruction, atenolol did not produce a significant increase in airways obstruction, whereas oxprenolol did. 4 Following isoprenaline challenge (1500 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

1978
1978
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 10 publications
1
16
0
1
Order By: Relevance
“…mean) ,-adrenoceptor blockers could therefore be unsafe. One of the criteria for the choice of the patients in this study was that they must exhibit bronchodilator response after 132-adrenoceptor agonist inhalation since it has been demonstrated that pulmonary function can only be reduced during P-adrenoceptor blockade in patients with reversible airway obstruction (Perks et al, 1978;Van Herwaarden, 1983). To ensure the clinical relevance of this study, the oral doses of bisoprolol and acebutolol (10 mg and 400 mg respectively), were those recommended in clinical practice for hypertension treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mean) ,-adrenoceptor blockers could therefore be unsafe. One of the criteria for the choice of the patients in this study was that they must exhibit bronchodilator response after 132-adrenoceptor agonist inhalation since it has been demonstrated that pulmonary function can only be reduced during P-adrenoceptor blockade in patients with reversible airway obstruction (Perks et al, 1978;Van Herwaarden, 1983). To ensure the clinical relevance of this study, the oral doses of bisoprolol and acebutolol (10 mg and 400 mg respectively), were those recommended in clinical practice for hypertension treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic airway obstruction usually display some deterioration in pulmonary function in response to ,-adrenoceptor antagonists, even the most 3,l-adrenoceptor selective (Perks et al, 1978;Sinclair, 1979;Dorow & Tonnesmann, 1984). Bisoprolol, a new ,-adrenoceptor antagonist without intrinsic sympathomimetic activity, has been demonstated to be highly Pl-adrenoceptor selective in animals and normal volunteers (Schliep & Harting, 1984;Leopold et al, 1986).…”
mentioning
confidence: 99%
“…However, compara-tive studies between different cardioselective 1-adrenoceptor blockers in asthmatic patients have shown little differences in their effect on airway calibre (Vilsvik & Schaanning, 1976;Lofdahl & Svedmyr, 1981). In patients with more fixed chronic airflow obstruction, cardioselective drugs have been shown to produce significantly less bronchoconstriction (Perks et al 1978;Sinclair, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, differences in the degree of selectivity of the cardioselective ,-adrenoceptor blockers since they displace to varying extents the bronchial dose-response curves to 32-adrenoceptor stimulants. In clinical studies, atenolol or bisoprolol appeared to be more selective than other compounds, such as acebutolol, metoprolol or oxprenolol (Greefhorst & van Herwaarden, 1982;Gribbin et al, 1981;Lammers et al, 1984;Lawrence et al, 1982;Macquin-Mavier et al, 1988;Perks et al, 1978;Ruffin et al, 1979;Tattersfield et al, 1984). Bronchial rings from a segmental bronchus were prepared and suspended in parallel in Krebs solution under an initial tension of 2.5 g. After 1.5 h of equilibration, the resting tension was between 1 and 2 g. Tensions were measured isometrically with strain gauges, amplifiers and .O.S..-Moise 2 recorder system (Celaster, Celle l'Evescault, 86600 Lusignan, France) (Advenier et al, 1986).…”
Section: Introductionmentioning
confidence: 99%